2016
DOI: 10.1016/j.athoracsur.2016.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Reintervention on the Autograft After Ross Procedure

Abstract: Autograft reintervention after a Ross appears to follow a bimodal distribution. Patients with primary autograft leaflet problems tend to present early without root dilatation and frequently require valve replacement. The autograft valve can be salvaged in the majority of patients who present later with root dilatation. Valve-sparing procedures are durable in the intermediate term and can be accomplished with low morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Compared with aortic mechanical valve replacement, the Ross procedure has various advantages, including no need for anticoagulation medication, autograft growth, and it has excellent hemodynamics. Although the Ross procedure has an acceptable long-term survival rate of over 80% [1,3,4], late complications are still unsatisfactory. Nelson et al showed that re-intervention in the long term is common for 87%, especially after 15 years of freedom from RVOT re-operation, which is around 53% [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with aortic mechanical valve replacement, the Ross procedure has various advantages, including no need for anticoagulation medication, autograft growth, and it has excellent hemodynamics. Although the Ross procedure has an acceptable long-term survival rate of over 80% [1,3,4], late complications are still unsatisfactory. Nelson et al showed that re-intervention in the long term is common for 87%, especially after 15 years of freedom from RVOT re-operation, which is around 53% [5].…”
Section: Discussionmentioning
confidence: 99%
“…Although the long-term results of the Ross procedure have been improving with acceptable low mortality, it is common that a re-intervention of the right ventricular outflow tract (RVOT) might be needed in the long term, in addition to treating aortic valve or aortic root [1,2]. However, an indicator of RVOT re-intervention is still unclear due to the lack of comprehensive assessment tools of right-sided heart hemodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Reintervention remains the main concern as there is a perception that the rates are high and this may be associated with increased morbidity and mortality ( 14 , 15 ). Reports on outcomes of reintervention after Ross however persistently demonstrated that it can be performed safely and that the autograft itself can sometimes be salvaged by repair or even valve-sparing reimplantation ( 31 33 ).…”
Section: Surgical Optionsmentioning
confidence: 99%
“…Re-intervention in the autograft root in the left ventricular outflow due to root dilation is more common in older patients and can often be addressed using valve-sparing approaches. 5 In these older patients, it appears that the orthotopic position of the reconstructed RVOT leads to better longevity. However, especially when the Ross procedure is undertaken in small children, the RVOT valve is unable to keep up with somatic growth and requires replacement over time.…”
mentioning
confidence: 99%